Proučevanje trajnostnosti turških provinc z uporabo mehke logike - Özmen, Ece (Urbani izziv, 2023)
Sustainability is the balance of social, economic, and environmental factors. Evolving from history to the present, the goal of this concept is for humanity to live in harmony with nature. Sustainable development, on the other hand, encompasses achieving urban goals for the future while increasing prosperity and effciently passing resources to future generations. Sustainability indicators are utilized to guide policymaking and monitor progress. Indicators introduced by various institutions vary by country. In developing economies like Turkey, which this study focuses on, there are a limited number of works on measuring sustainability performance. Hence, this study evaluates urban sustainability levels using the fuzzy logic method. Another objective is to develop a measurable and replicable numerical model to analyse the sustainability performance of cities in Turkey. The study employs a measurement set consisting of twenty-seven indicators from the main ecological, economic, and social components, and it assesses the sustainability levels of cities using fuzzy logic rules. Based on the results obtained, all eighty-one provinces of Turkey are classified into quantile groups and mapped. This analytical approach can guide urban planners, policymakers, and decision-makers. is study contributes to enhancing knowledge and understanding sustainability
Keywords: fuzzy logic; mehka logika; sustainability; sustainable cities; trajnostna mesta; trajnostnost; Turčija; Turkey